Clinico-Epidemiological study of childhood vitiligo and its associations: A hospital-based cross-sectional study - Fatima Tuz Zahra; Syed Suhail Amin; Mohammad Adil; Fariz Sarshar; Prateek Pathak (Wolters Kluwer Medknow Publications, 2022)
Background: Vitiligo is a chronic pigmentary disorder resulting in hypopigmentary areas which progressively become amelanotic. The onset of vitiligo in childhood leads to severe psychological trauma to both patients and their parents. Aim: The aim was to study the clinical profile of childhood vitiligo (<18 years) and its association with other autoimmune diseases. Materials and Methods: It was a cross-sectional study of 256 clinically diagnosed childhood vitiligo cases over a period of two years. Detailed history of disease onset, duration, progression, associated diseases, and family history was recorded after informed consent from parents/guardians. Assessment of vitiligo was done by Vitiligo Area Severity Index (VASI). Results: Of the total 256 patients, females (n = 149) outnumbered males (n = 107) with a mean age of 9.80 ± 4.59 years with a mean disease duration of 1.9 years. The most common morphological type was vitiligo vulgaris (48.8%), while the most common site of disease onset was face (30.5%). Positive family history was seen in 49 patients (19.1%) and Koebner phenomenon in 54 patients (21.1%). The mean VASI score was 1.64. Conclusion: Childhood vitiligo is more common in females with anemia present in significant number of cases. Premature canities is the most common cutaneous association. Thyroid dysfunction was seen in nonsegmental variant. Children with the positive family history of vitiligo had higher mean VASI than those with the negative family history (P = 0.002).